Recurrent Syncope in a Cancer Patient: A Case Report and Review of the Literature - Jyoti Sharma; Anne H. Dougherty (Cardiology Research and Practice)
A 59-year-old male with invasive squamous cell carcinoma of the left preauricular region, treated with several chemotherapy regimens and radiation therapy, was admitted for recurrent syncopal episodes. He was found to be suffering from neurocardiogenic reflex-mediated syncope secondary to mechanical compression of the carotid baroreceptors and glossopharyngeal nerve by the tumor. We discuss the pathophysiology of this case and the available treatment options.